Sistem Pengambilan Keputusan Penentuan Lokasi Beauty Shop Menggunakan Metode Simple Additive Weighting (SAW) (Yayasan Kawanad, 2022)
The purpose of this study was to design and develop a decision support system for the location of a salon or beauty shop in Aceh Province. In this study, the authors used observation and interview techniques by implementing SAW in the analysis and waterfall as a software development method. This study succeeded in making a Decision Making System for Determining Salon Business Locations in Aceh Province Using the SAW Method and this study succeeded in performing alternative rankings from the weight calculation results for Determining Salon Business Locations in Aceh Province using SAW (Simple Additive Weighting). The suggestions that the author wants to convey after making observations are for further development, the system is expected to be able to combine several other methods as a comparison of alternative ranking results and need further development in the reporting process, because this system is still very simple in displaying reports so that in the future there will be more use more detailed graphics.